2020
DOI: 10.1177/0954411920940829
|View full text |Cite
|
Sign up to set email alerts
|

Tribological behavior of dental restorative composites in chewable tobacco environment

Abstract: This study investigates the effect of smokeless tobacco on the tribological properties of two commercially used dental composite materials: Tetric N-Ceram and Z350 Dentin shade. It is to evaluate the effect of smokeless tobacco on the wear properties of two dental composite materials after some stipulated period. The wear test was conducted on pin-on-disk tribometer in the presence of artificial saliva under different loading conditions of 10, 15 and 20 N. The pins of the dental composite material wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…The mechanical properties of dental composite material are less sensitive to temperature changes in the real oral environment [63,64,109]. The long-term tobacco environment also influences the mechanical and tribological properties of dental restorative materials [110][111][112][113]. Also, the contamination by cigarette smoke decreases the bond strength between dentin and composite resin [114].…”
Section: Effects Of Ph Environmentmentioning
confidence: 99%
“…The mechanical properties of dental composite material are less sensitive to temperature changes in the real oral environment [63,64,109]. The long-term tobacco environment also influences the mechanical and tribological properties of dental restorative materials [110][111][112][113]. Also, the contamination by cigarette smoke decreases the bond strength between dentin and composite resin [114].…”
Section: Effects Of Ph Environmentmentioning
confidence: 99%
“…No animal or human studies were identified. The included studies are listed in the Table 1 [22,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. The number of publications increased through the years and 13 of 17 articles were published after 2010.…”
Section: Study Selectionmentioning
confidence: 99%
“…The number of publications increased through the years and 13 of 17 articles were published after 2010. In addition, 13 studies were published in journals that covered research into mechanical engineering or technology of nanosized and nanostructured materials, including advanced ceramic materials and reinforced plastics and polymer composites [25][26][27][28][29][30][31][32][33][35][36][37][38]; three studies were published in journals that focused on the application of biomaterials and tissue engineering in the medical sciences [24,34,39] and only one was published in a dentistry journal [22].…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations